KEDUDUKAN HUKUM PRIA DALAM MENGAKSES SISTEM ELEKTRONIK DI LAPTOP YANG DIIZINKAN TEMAN PEREMPUANNYA (Legal status of men accessing electronic systems on laptop which are permitted by Female Friend) - Parlindungan Satria (President University, 2019)
Information Technology, media and communication role has changed society and human civilization behaviour globally. Information and communication technology development is very quick and world relations are borderless, further significant social, economic and cultural changes are quickly. The impact of information technology contributes to welfare, progress and society civilization as well as acts against the law.The man and his girlfriend used information and communication technology facilities in which the man lend her a